ANALISIS RETURN SAHAM, ABNORMAL RETURN DAN TRADING VOLUME ACTIVITY TERHADAP PENGUMUMAN MERGER DAN AKUISISI (Study Kasus Pada Perusahaan Yang Terdaftar di Bursa Efek Indonesia Periode 2010-2014) - Nurul Qomariah; Haryetti Haryetti; Errin Yani Wijaya (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aims to known different between stock return, abnormal return, and trading volume activity before and after merger and aquisition announcement to company listed in Indonesian Stock Exchange in the period 2010-2014. In this research, it used purposive sampling method, that it take from all company listed in Indonesian Stock Exchange which is give merger and aquisition announcement as many 259 company. Based on set criteria the sample in this research are 53 company, the statistical test used is paired samples t-test on the period before and after the event. This research shows the stock return, abnormal return, and trading volume activity analysis before and after announcement of merger and aquisition shows that is not significant different.Keywords: Merger and Aquisition, Stock Return, Abnormal Return, and Trading Volume Activity (TVA)